"Landholding‐patriarchy hypothesis" and women's autonomy in rural India. Issue 3 (2014) - Srinivas Goli; Ladumai Maikho Apollo Pou
<x xml:space="preserve"> Abstract </x> Purpose – The paper aims to find out how far the size of household landholding directs patriarchal traits and thus influence women's autonomy. Design/methodology/approach – The study used a two‐part methodology. The first part provides theoretical background based on existing literature on women's autonomy and related information in formulating the "landholding‐patriarchy hypotheses". The second part of this study evaluates the empirical evidences of the association between the size of household landholding and women's autonomy. Findings – Results indicate considerable variation in women's autonomy with the size of their household landholding: women's autonomy decreases with increasing size of household landholding. Evidence suggests that landholding directs patriarchal traits, as manifested in a reasonable influence on women's autonomy in rural India. Originality/value – The paper innovates a means to understand the contributing factors to lowering women's autonomy, thus explore the relevance of "landholding‐patriarchy hypothesis".